2009
DOI: 10.1097/mou.0b013e328323f5ed
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of organ-confined prostate cancer: functional ultrasound, MRI and PET/computed tomography

Abstract: Considerable advances have been made in the identification of organ-confined prostate cancer with multiparametric MRI. Only prebiopsy MRI can provide best quality of cancer assessment and allows for targeting biopsies. It is hoped that advances in 3T MRI as well as in radiotracers for PET/computed tomography will further improve diagnosis, treatment selection, planning and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 81 publications
0
28
1
Order By: Relevance
“…This type of MRI is performed by injecting a gadolinium based contrast agent into the patient and measuring the signal intensity on T1 weighted images. Areas of increased angiogenesis, such as prostate cancer, will have increased enhancement on T1 weighted images [Puech et al 2009;Kurhanewicz et al 2008]. A recent study showed that DCE MRI has a 89% sensitivity and 90% specificity for localizing prostate cancer [Crawford and Barqawi, 2007].…”
Section: Future Direction Of Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…This type of MRI is performed by injecting a gadolinium based contrast agent into the patient and measuring the signal intensity on T1 weighted images. Areas of increased angiogenesis, such as prostate cancer, will have increased enhancement on T1 weighted images [Puech et al 2009;Kurhanewicz et al 2008]. A recent study showed that DCE MRI has a 89% sensitivity and 90% specificity for localizing prostate cancer [Crawford and Barqawi, 2007].…”
Section: Future Direction Of Researchmentioning
confidence: 99%
“…A minimum of six weeks is required between the prostate biopsy and the MRI. Prostatic hemorrhage after biopsy can cause artifact that will overestimate the amount of cancer on the MRI [Puech et al 2009;Zelhof et al 2009;Kurhanewicz et al 2008].…”
Section: Future Direction Of Researchmentioning
confidence: 99%
See 3 more Smart Citations